Understanding and identifying barriers to electric vehicle adoption through thematic analysis. (June 2021) - Krishna, G.
Highlights: Intangible factors of adoptions were found which has cultural importance amongst consumers. Thematic network of factors shows the interdependency amongst factors forming collective barriers. Qualitative analysis shows clearer understanding of the barriers and provides contextual data to understand the barriers. Qualitative analysis of eWOM is used, as it does not restrict consumers to few options like surveys. Abstract: The study aims to understand the general perception of electric vehicles among consumers and the barriers to their widespread adoption. The study focuses on identifying and understanding the factors involved in their purchase with a wider range of expression using thematic analysis unlike traditional survey techniques. Further, the role of emotions is also considered in the study which is normally overlooked. eWOM is used as data for the study as it is relevant for electric vehicles as people majorly use internet mediums to freely share their thoughts. This method helps in finding all gaps (tangible and intangible) present in the offering (EVs) and expectations of a consumer. This study also provides us with information on relationships amongst these barriers which has a negative cascading effect on overall adoption.